Development of active power filter using rectifier boost technique - Baharom, Rahimi (2006)
This project concern with the study of a method for the reduction of harmonic distortion in power systems that have the non-linear load. These project develop active power filter using rectifier boost technique to eliminate the harmonic problems. The technique of a single-phase diode bridge rectifier with the capacitor filter, followed by a boost stage containing only one switch and one boost-inductor. This strategy results the eliminating of the harmonic distortions and will be improve the power factor to unity of the rectifier circuit. This is achieved through the use of boost technique in wave shaping the supply current to be sinusoidal and in-phase with the supply voltage. This compensation strategy is analyzed using PSIM and verified in experimental implementation. The results show close agreement between the simulation and experimental explorations.